ANALISIS SALURAN PEMASARAN USAHATANI JAGUNG HIBRIDA DI DESA JAYA MAKMUR KECAMATAN LABANGKA - Novika Komalasari; Alia Wartiningsih; Lukman Hakim; Muhammad Aries Zukhri Angkasa; Yadi Hartono (Alia Wartiningsih, M.Si, 2025)
This study aims to: (1) analyze the marketing channels of hybrid maize in Jaya Makmur Village, Labangka District; and (2) analyze the farmer's share, marketing margin, and marketing efficiency of hybrid maize in Jaya Makmur Village, Labangka District. The research was conducted in April 2025. Respondents were selected using a purposive sampling technique. The study population consisted of 1,157 farmers from 28 farmer groups. Seven farmer groups were selected based on the criterion that they had the largest membership (more than 55 members). The sample size was determined using quota sampling by selecting five respondents from each farmer group, resulting in a total of 35 respondents. The data were analyzed using Farmer's Share, marketing margin, and marketing efficiency analyses. The results showed that there were two hybrid maize marketing channels in Jaya Makmur Village, Labangka District. The first marketing channel was: farmers ? district-level wholesaler (PT. Segar Agro Nusantara). The second marketing channel was: farmers ? village collector ? district-level wholesaler (PT. Segar Agro Nusantara). The Farmer's Share was 60% for the first marketing channel and 53% for the second marketing channel. The total marketing margin in the first marketing channel was IDR 0, while the marketing margin in the second marketing channel was IDR 400/kg. The marketing efficiency of the first marketing channel was 0.08 (8%), whereas that of the second marketing channel was 0.09 (9%). Therefore, the first marketing channel was more efficient than the second because longer marketing channels incur higher marketing costs, resulting in higher prices paid by consumers.